Prototype-Design of Soil Movement Detector Using IoT Hands-on Application - Reza Diharja; Muhammad Reza Fahlevi; Endang Sri Rahayu; Wike Handini (Postgraduate, University of Mataram, 2022)
The landslide disaster that killed people occurred due to public ignorance of the type of soil prone to landslides. Several efforts have been made to create prototype tools for soil movement detection. However, researchers using the Internet of Things (IoT) technology are still limited. The IoT allows for the transmission of data over an internet connection, is always connected, offers remote control capabilities, and data sharing. All of this served as the prototype design of foundation for the soil movement detection. A light-based proximity sensor is used in system, and its output is represented as a movement of the soil on an inclined plane. F furthermore, the data used as input for the NodeMCU ESP8266 microcontroller is linked to the internet. The output is an HMI in the form of an LCD monitor that displays the soil movement measurement. The simulation of disturbances in an inclined plane is done differently depending on the frequency and duration. Moreover, monitoring is carried out by transferring processed data to the Blynk platform, which is subsequently shown in real time via the Blynk Android application. The test results of the tool used three distinct samples, as well as varied disturbance frequencies and durations. With the soil samples, the biggest movement data was 5cm achieved at a disturbance frequency of 5Hz and 40 seconds duration. The largest movement data for sand samples was 11cm at a disturbance frequency of 3Hz and 50 seconds duration, followed by largest movement data for sand soil mixture samples was 8cm at a disturbance frequency of 5Hz and 50 seconds duration. People should not reside on slopes, especially if the soil's primary component is sand.